The use of hydrogen as an alternative fuel in urban transport - Vilke, Siniša (Array, 2020)
This paper shows the analyses of hydrogen vehicles within urban centres, which have been gaining increasing importance lately. In fact, due to the negative impact of conventional vehicles on human health and environment, the need is imposed for implementation of eco-powered vehicles that also tend to be sustainable in transport. Gradual removal of fossil fuels and the use of alternative road transport technologies are among the primary objectives of most countries. This paper aims to examine the impact of hydrogen technology in urban transport, ie to point out how hydrogen vehicles have affected the satisfaction of customers and users through individual projects. Furthermore, the paper analyses the current situation in the application of hydrogen vehicles in the world, as well as future investments in infrastructure through strategies aimed at boosting higher demand for clean energy.